Comparison of Outcomes Between Suture Button Technique and Screw Fixation Technique in Patients With Acute Syndesmotic Diastasis: A Meta-analysis of Randomized Controlled Trials. Issue 4 (December 2021) - Ramadanov, Nikolai; Bueschges, Simon; Dimitrov, Dobromir
Background: Our aim was to compare the outcome between suture button (SB) stabilization and syndesmotic screw fixation (SF) in patients with acute syndesmotic diastasis. Methods: A systematic literature search up to June 30, 2021, was performed to identify randomized controlled trials (RCTs) comparing outcomes of SB with SF techniques in patients with acute syndesmotic diastasis. We calculated mean differences for continuous outcomes, using the Hartung-Knapp-Sidik-Jonkman method, and odds ratio for dichotomous outcomes, using the Mantel-Haenszel method. Results: Eight RCTs involving 569 patients met the inclusion criteria, 1 RCT with level I evidence, and 7 RCTs with level II evidence. The meta-analysis showed that the SB technique had a higher AOFAS score <6 months and 12 months postoperatively (MD = 4.74, 95% CI 1.68-7.80, P = .01; and MD = 5.42, 95% CI 1.50-9.33, P = .02) and reduced the risk of implant irritation (OR = 0.31, 95% CI 0.11-0.89, P = .03), implant failure (OR = 0.06, 95% CI 0.02-0.23, P < .01), and reoperation (OR = 0.43, 95% CI 0.22-0.83, P = .01). The 2 approaches did not differ in further functional outcomes or postoperative complications. Conclusion: Because functional outcomes showed no relevant difference between both SB and SF, the advantage of SB appears to be in the lower risk for postoperative complications. The SB technique led to fewer cases of implant irritation, implant failure, and reoperation compared with SF. Level of Evidence: Level I, meta-analysis of RCTs.